2001
DOI: 10.1002/1099-0682(200109)2001:9<2227::aid-ejic2227>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Thiomolybdenyl Complexes − Synthesis and Structural and Spectroscopic Characterization

Abstract: The first series of mononuclear thiomolybdenyl complexes, Tp*Mo V SX 2 [Tp* = hydrotris(3,5-dimethylpyrazol-1-yl)borate, X/X 2 = anion/dianion], has been prepared. The complexes, which have been characterized by analytical, mass

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…2.128 Å) and anionic co‐ligand X groups; the structure of [Tp*MoS(bdt)] (Figure ) is representative . The presence of a terminal sulfido ligand is confirmed by the observation of strong S K‐pre‐edge features assigned to S 1s →π*(S 3p + Mo 4d ) transitions …”
Section: Stabilization and Electronic Structure Of Oxido‐mo Dithiomentioning
confidence: 86%
See 1 more Smart Citation
“…2.128 Å) and anionic co‐ligand X groups; the structure of [Tp*MoS(bdt)] (Figure ) is representative . The presence of a terminal sulfido ligand is confirmed by the observation of strong S K‐pre‐edge features assigned to S 1s →π*(S 3p + Mo 4d ) transitions …”
Section: Stabilization and Electronic Structure Of Oxido‐mo Dithiomentioning
confidence: 86%
“…The derivatization of [Tp*MoSCl 2 ] has also been reported since 2000 and this has permitted structural and spectroscopic studies of sulfido‐Mo V species, [Tp*MoSX 2 ] {X = phenolate derivative; X 2 = catecholate (cat 2– ), bdt 2– , tdt 2– }, and their comparison to the oxido analogues above , . The sequence of reactions leading to [Tp*MoSX 2 ] is shown in Equation ; it involves sulfidation of 35 to produce [Tp*MoSCl 2 ] 41 followed by metathesis with the triethylammonium salts of X – /X 2 2– to give desired [Tp*MoSX 2 ] 42 .…”
Section: Stabilization and Electronic Structure Of Oxido‐mo Dithiomentioning
confidence: 99%
“…46 × 10 −4 cm −1 and 37 × 10 −4 cm −1 for hard and soft ligand donors, respectively). 3,64,65 The spectra are also distinct from those reported for various dioxo-Mo(V) analogues, [Tp x MoO 2 X] − ; these complexes contain two strong field oxo ligands in a cis configuration and exhibit highly anisotropic spectra (Δg ca. 0.15−0.18) with lower g iso (∼1.90−1.93) and marginally higher A iso (∼40−45 × 10 −4 cm −1 ) values (especially when comparing analogous pairs of compounds).…”
Section: Inorganic Chemistrymentioning
confidence: 76%
“…FDH catalyzes the oxidation of formate to CO 2 and a detailed description of the important biological processes that control the different chemical properties of molybdenum and tungsten to tune the reactivity, substrate specificity and metabolic role of FDHs has appeared recently. 56,57 A re-evaluation 68 of the previous X-ray structural analysis 69 of Mo-FDH active site showed that the [70][71][72][73] The usual problem of redox and hydrolysis reactions of Mo IV S units that leads to the formation of polynuclear complexes was avoided by use of sterically demanding tridentate ligands. However, use of nondithiolene ligands does not mimic the MPT ligand present in the active site.…”
Section: Perspectivementioning
confidence: 99%